2009
DOI: 10.1093/eurheartj/ehn529
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, determinants, and prognostic value of reverse left ventricular remodelling after primary percutaneous coronary intervention: results of the Acute Myocardial Infarction Contrast Imaging (AMICI) multicenter study

Abstract: AimsFew data are available on the extent and prognostic value of reverse left ventricular remodelling (r-LVR) after ST-elevation acute myocardial infarction (STEMI). We sought to evaluate incidence, major determinants, and long-term clinical significance of r-LVR in a group of STEMI patients treated with primary percutaneous coronary intervention (PPCI). In particular, the role of preserved microvascular flow within the infarct zone in inducing r-LVR has been investigated.Methods and resultsSerial echocardiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
89
1
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(96 citation statements)
references
References 29 publications
(57 reference statements)
3
89
1
2
Order By: Relevance
“…[8][9][10] The earlier the onset-toreperfusion time, the greater the degree of LV salvage can be expected, which results in prompt LV improvement and then chronic reverse remodeling of the LV. In the present study, we separately showed the dynamics of IMR in (1) the early stage and (2) the follow-up period after PCI as an effect of the emergency reperfusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10] The earlier the onset-toreperfusion time, the greater the degree of LV salvage can be expected, which results in prompt LV improvement and then chronic reverse remodeling of the LV. In the present study, we separately showed the dynamics of IMR in (1) the early stage and (2) the follow-up period after PCI as an effect of the emergency reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Primary percutaneous coronary intervention (PCI) for AMI can provide dynamic improvement of left ventricular (LV) function, [8][9][10] which should dramatically affect the magnitude of IMR. Although some recent studies have reported the prognostic value of the IMR 11,12 or the effect of revascularization on the degree of IMR in patients who underwent PCI, [13][14][15][16][17] serial dynamics of IMR from the emergency room (ER) to followup period after PCI has yet to be investigated.…”
Section: See Editorial By Sannino and Grayburn See Clinical Perspectivementioning
confidence: 99%
“…Dotyczy to zwłaszcza tych osób, u których przedoperacyjne badania obrazowe wskazywały na obecność niedokrwionego lub zahibernowanego mięśnia sercowego [291,292]. U większości pacjentów ze znacznym zmniejszeniem LVEF bezpośrednio po przebyciu STEMI obserwuje się istotną poprawę czynności skurczowej po 3 miesiącach [286].…”
Section: Zalecenia Dotyczące Optymalnej Strategii Postępowaniaunclassified
“…Recently, the AMICI multicenter study showed that reverse remodeling frequently occurs in ST-segment elevation in MI patients treated with primary PCI and is an important predictor of favorable long-term outcome. A preserved microvascular perfusion within the infarct zone is the major determinant of reverse remodeling [75].…”
Section: Reverse Remodelingmentioning
confidence: 99%